Determinants of Insecticide-Treated Net Utilization for Malaria Prevention Among Under-Five Children in The Gambia: Evidence From National Survey - Amadou Barrow; Bakary Kinteh; Mansour Badjie; Amadou Kongira; Ayodeji Matthew Adebayo; Rex A. Kuye; Edrisa Sanyang (Journal of Tropical Medicine)
Conclusion: This study elucidates the complex factors influencing ITN utilization among children under 5 years of age in The Gambia. The nuanced understanding of individual-, household-, and community-level factors offers a robust foundation for targeted strategies for malaria prevention, with far-reaching implications for public health policy and practice.